Laying the groundwork for in-class groupwork with readings beyond the textbook. Issue 4 (4th August 2021) - Ruder, Phil
Abstract: The author of this article describes individual pre-class and group in-class assignments based on current news articles. Guided student pre-class readings of periodical articles can form the basis for engaging in-class group assignments. Many economics instructors seek to develop student skills at applying the concepts under study to analyze current events, but news articles can be difficult for novices because the economic content is often misconstrued by journalists and is presented along with many extraneous details. Assigning short-essay questions with the readings can help students identify the economic content while holding them accountable for the assignment. The complexity of event analysis based on news article readings makes these readings excellent material for engaging students in in-class group assignments that build on the individual student preparation.